Does adult education at upper secondary level influence annual wage earnings? - Anders Stenberg (Institute for Labour Market Policy Evaluation (IFAU), 2007)
Adult education at upper secondary level (AE) is an integral part of the Swedish educational system. Of the cohort born in 1970, about one third has at some point been registered in AE. This evaluation of AE is the first to use register data on the course credits actually attained. The results indicate that credits equal to one year of AE yield point estimates that range from 5 per cent for individuals with prior two-year upper secondary school to 15 per cent for those with prior compulsory school. The positive effects are mainly driven by courses in health related subjects and computer science. Of the participants in AE, more than 40 per cent continue to university. The returns to years in higher education are not found to be different between individuals with and without a prior AE registration except for those with one year or less at university.
Keywords: H52; J68; 330; Adult education; wage earnings; Erwachsenenbildung; Bildungsabschluss; Bildungsertrag; Lohn; Bildungsökonomik; Schweden